Spiritual Improvement of the Community Through the Study of Kitab Kuning and Wirid Ratib Al-Haddad - Syaiful Mustofa; Abdullah Ubaid; A. Syamsul Ma’arif; Suci Ramadhanti Febriani; Ayu Desrani (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
This study aims to explore the improvement of spiritual and social ethics through the learning of the Kitab kuning and Wirid Readings in Merjosari Lowokwaru Village, Malang City. This study used a Participatory Action Research (PAR) approach, the sampling technique used purposive sampling, the data analysis technique used is triangulation, and the research methods used are observation, documentation, and interviews. Researchers found that the Merjosari community's spiritual quality and social ethics were substantially impacted, as evaluated by the frequency, quantity, and intensity of the five daily prayers. The excitement of community members participating in the survey increases every day, indicating that the increase in social ethics is rising. Some respondents requested that the study be repeated once a week as a habit. As seen by the frequency of questions on numerous themes, the residents of Merjosari understand the content of the kitab kuning. The inhabitants of Merjosari can comprehend Ratibul Haddad's Wirid.